(3GdeOhfIs - (3CHh YHO Gddg YHO GdQMef GHf GdbGSe GdeGdcj,J (B191 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdUQa s
(3BNQgG (B:s
(3Je cJGH GdJOdjS HGdYjhH HMeO Gddg hYhfg hMSf Jhajbg hjdjg cJGH GdESQGA s
(3CHhGH ef GdHjhYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1644s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQjI (B((3eGdcj (B868) s
Keywords: (3Gdabg GdeGdcjs